Comparative study of photoinitiators for the synthesis and 3D printing of a light-curable, degradable polymer for custom-fit hard tissue implants. (11th December 2020) - Shakouri, Taleen; Cha, Jae-Ryung; Owji, Nazanin; Haddow, Peter; Robinson, Thomas E; Patel, Kapil D; García-Gareta, Elena; Kim, Hae-Won; Knowles, Jonathan C
Abstract: Three-dimensional (3D) printing enhances the production of on-demand fabrication of patient-specific devices, as well as anatomically fitting implants with high complexity in a cost-effective manner. Additive systems that employ vat photopolymerisation such as stereolithography (SLA) and digital light projection are used widely in the field of biomedical science and engineering. However, additive manufacturing methods can be limited by the types of materials that can be used. In this study, we present an isosorbide-based formulation for a polymer resin yielding a range of elastic moduli between 1.7 and 3 GN mm −2 dependent on the photoinitiator system used as well as the amount of calcium phosphate filler added. The monomer was prepared and enhanced for 3D-printing using an SLA technique that delivered stable and optimized 3D-printed models. The resin discussed could potentially be used following major surgery for the correction of congenital defects, the removal of oral tumours and the reconstruction of the head and neck region. The surgeon is usually limited with devices available to restore both function and appearance and with the ever-increasing demand for low-priced and efficient facial implants, there is an urgent need to advance new manufacturing approaches and implants with a higher osseointegration performance.